Silence Is Violence, and So Is Speech. Issue 1 (2nd January 2022) - Shafer, Matt
Abstract: This synoptic essay reflects on contemporary impasses in the cultural politics of language. I argue that current controversies about linguistic violence reflect an unresolved tension between two distinct registers in which debates about language operate. One framework, best characterized in terms of the basic categories of discourse and power, is oriented toward the critique of structure; the other, which instead emphasizes speech and harm, is oriented toward the criticism of behavior. I contextualize both sensibilities historically and argue that the tension between them is itself a symptom of deeper dynamics in contemporary political life. We cannot resolve debates about linguistic violence simply through conceptual analysis or reinterpretation; instead, we must reexamine how language itself is being transformed by more fundamental kinds of social, political, and technological change.